2020
DOI: 10.1111/apt.15826
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism genetic risk score to aid diagnosis of coeliac disease: a pilot study in clinical care

Abstract: Summary Background Single nucleotide polymorphism–based genetic risk scores (GRS) model genetic risk as a continuum and can discriminate coeliac disease but have not been validated in clinic. Human leukocyte antigen (HLA) DQ gene testing is available in clinic but does not include non‐HLA attributed risk and is limited by discrete risk stratification. Aims To accurately characterise both HLA and non‐HLA coeliac disease genetic risk as a single nucleotide polymorphism–based GRS and evaluate diagnostic utility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…In diseases where one variant has the predominant effect on genetic risk e.g., HLA-DQ in coeliac disease, it might be possible to estimate prevalence using just this variant. However previous work has shown a GRS including the predominant variant as well as smaller effect variants has better discriminative ability than the predominant variant alone [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In diseases where one variant has the predominant effect on genetic risk e.g., HLA-DQ in coeliac disease, it might be possible to estimate prevalence using just this variant. However previous work has shown a GRS including the predominant variant as well as smaller effect variants has better discriminative ability than the predominant variant alone [15].…”
Section: Discussionmentioning
confidence: 99%
“…For each included genotype at the DQ locus, the odds ratio was derived from a previously described case-control dataset [18]. For each non-HLA locus, odds ratios from existing literature were used, and each weight was multiplied by individual risk allele dosage [15, 18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the recent article by Sharp et al describing a single nucleotide polymorphism (SNP) genetic risk score (GRS) for coeliac disease 1 . The authors reported a 42 SNP model, combining the four established HLA risk alleles for coeliac disease (DQ2.5, DQ2.2, DQ8 and DQ7.5) and 38 non‐risk variants, which achieved a similar quality of prediction (AUC = 0.875) as the best previously reported GRS model with several hundreds of SNPs (AUC = 0.87‐0.89) 2 .…”
Section: Figurementioning
confidence: 99%
“…However, the possible use of non-HLA variants for the stratification of celiac patients has not yet been introduced in the clinical setting (Figure 1). A recent study selected 42 SNPs from a European case control study of about 12,000 patients and as many controls and showed that these SNPs can discriminate celiac disease more than HLA-DQ2/DQ8 in both adults (1,280 cases) and children (114 cases) cohorts (35). Moreover, since clinical presentation of celiac disease differs in siblings with similar HLA haplotypes, it has been suggested that non-HLA genes may play a significant role more so than HLA-concordance in siblings (36).…”
Section: Genetic Variants Of Non-hla Loci Associated With Celiac Diseasementioning
confidence: 99%